Secondary Metabolism and Hormone Response Reveal the Molecular Mechanism of Triploid Mulberry (Morus Alba L.) Trees Against Drought - Liu, Hui; Sun, Hongmei; Bao, Lijun; Han, Shuhua; Hui, Tian; Zhang, Rui; Zhang, Minjuan; Su, Chao; Qian, Yonghua; Jiao, Feng (Frontiers in Plant Science, 2021)
The improvement of plant’s resistance to drought is a major endeavor in agriculture. Polyploid plants often exhibit enhanced stress tolerance relative to their diploid progenitor, but the matching stress tolerance is still little understood. Own-rooted stem cuttings of ShinIchinose (2n=2X=28) and Shaansang-305 (2n=3X=42) were used in this study, of which the latter (triploid) is a more valuable autotriploid mulberry tree than the former (diploid) because it is a better cultivar for both production and application purposes. Here, a drought stress treatment was applied and the responses of triploid Shaansang-305 and diploid progenitor ShinIchinose were compared through an investogation of their physiological traits, RNA-seq, and secondary metabolome analysis. The results showed that the triploid exhibited an augmented ABA (abscisic acid) content under drought conditions and a superior stress-resistance phenotype under severe drought stress when compared with the diploid. Interestingly, some genes (TSPO, NCED3, LOC21398866) and ATG gene related to ABA signaling showed significantly upregulated expression in the triploid mulberry. Further, the triploid accumulated higher levels of RWC and SOD activity, as well as more wax on the leaf surface, than did the diploid under water-restricted growing conditions, but with more reductive flavonoid in diploid. Our results suggest the possibility of ploidy levels being linked to drought resistance, in that triploid plants may better cope with drought events. Furthermore, the flavonoid metabolism involved in drought resistance identified here may be of great value to medicinal plants. The findings presented here could have substantial implications for future studies of crop breeding.